Books Bought and Books Actually Read: Mecmuas as Sources for the History of Reading in the Ottoman Empire - Paić-Vukić, Tatjana (2013)
The paper examines the possibilities and limitations of the research into Ottoman personal notebooks as sources for the history of reading.